1974
DOI: 10.1159/000260095
|View full text |Cite
|
Sign up to set email alerts
|

Serum Complement-Fixing Antibodies in Human Dental Caries

Abstract: The relationship between serum complement-fixing antibodies against streptococcal cell walls and the incidence of caries was studied in 116 subjects. The series was divided into an ‘active caries’ (AC) group and a ‘caries-free and treated caries’ (CFTC) group, and the antibody titres were correlated with the index of decayed, missing and filled (DMF) teeth. In the CFTC group, a significant negative correlation coefficient was found with three strains of Streptococcus mutans which have been shown to be cariogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1975
1975
1991
1991

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…With IgG a significant positive correlation was found only in the AC group but further analysis showed that this correlation was not statistically different from that found in the NDC group. It is possible that serum IgG rises following the development of carious lesions and this would be consistent with the finding of a positive correlation between ser um IgG complement-fixing antibodies and the DMF index in subjects with carious lesions [Challacombe, 1974].…”
Section: Discussionsupporting
confidence: 76%
“…With IgG a significant positive correlation was found only in the AC group but further analysis showed that this correlation was not statistically different from that found in the NDC group. It is possible that serum IgG rises following the development of carious lesions and this would be consistent with the finding of a positive correlation between ser um IgG complement-fixing antibodies and the DMF index in subjects with carious lesions [Challacombe, 1974].…”
Section: Discussionsupporting
confidence: 76%
“…Antibodies to S. mutans have been detected in hu man serum [Challacombe, 1974] and these can reach the gingival crevice via the crevicular fluid [Challa combe et al, 1978], Serum Ig has been demonstrated by IF staining in the apical plaque border on approxi mal tooth surfaces [Newman et al, 1979]. Emilson et al [1974] suggested that such host Ig could affect the reliability of the IF technique if it masked bacterial antigens.…”
Section: Discussionmentioning
confidence: 99%
“…This inverse correlation has been interpreted as a protective effect of the IgG antibodies [Kennedy et ai., 1968;Challacombe et al, 1973;Challacombe, 1974;Lehner et al, 1978;Challacombe et al, 1984b], In some studies the opposite was found, i.e. higher serum IgG antibody activity in caries-active persons than in ca ries-free [Lehner etal., 1970;Huisin't Veld et al, 1979].…”
Section: Immunization Routes and Effectsmentioning
confidence: 99%